Projecting the direct cost burden of osteoarthritis in Canada using a microsimulation model. Issue 10 (October 2015) - Sharif, B.; Kopec, J.; Bansback, N.; Rahman, M.M.; Flanagan, W.M.; Wong, H.; Fines, P.; Anis, A.
Summary: Objectives: To estimate the future direct cost of OA in Canada using a population-based health microsimulation model of osteoarthritis (POHEM-OA). Methods: We used administrative health data from the province of British Columbia (BC), Canada, a survey of a random sample of BC residents diagnosed with OA (Ministry of Health of BC data), Canadian Institute of Health Information (CIHI) cost data and literature estimates to populate a microsimulation model. Cost components associated with pharmacological and non-pharmacological treatments, total joint replacement (TJR) surgery, as well as use of hospital resources and management of complications arising from the treatment of osteoarthritis (OA) were included. Future costs were then simulated using the POHEM-OA model to construct profiles for each adult Canadian. Results: From 2010 to 2031, as the prevalence of OA is projected to increase from 13.8% to 18.6%, the total direct cost of OA is projected to increase from $2.9 billion to $7.6 billion, an almost 2.6-fold increase (in 2010 $CAD). From the highest to the lowest, the cost components that will constitute the total direct cost of OA in 2031 are hospitalization cost ($2.9 billion), outpatient services ($1.2 billion), alternative care and out-of-pocket cost categories ($1.2 billion), drugs ($1 billion), rehabilitation ($0.7 billion) and side-effect of drugs ($0.6 billion). Conclusions: Projecting the future trends in the cost of OA enables policy makers to anticipate the significant shifts in its distribution of burden in the future.